Toll-Like Receptor 4–Myeloid Differentiation Primary Response Gene 88 Pathway Is Involved in the Inflammatory Development of Polymyositis by Mediating Interferon-γ and Interleukin-17A in Humans and Experimental Autoimmune Myositis Mouse Model - Zhang, Hongya; He, Fangyuan; Shi, Ming; Wang, Wenxiu; Tian, Xiaojia; Kang, Juan; Han, Wenjuan; Wu, Rui; Zhou, Linfu; Hu, Mengmeng; Li, Xiaobo; Mi, Fang; et al. (Frontiers in Neurology, 2017)
Objective: Toll-like receptor 4 (TLR4) is one of key players in the development of many autoimmune diseases. To determine the possible role of TLR4 in polymyositis (PM) development, we collected muscle samples from PM patients and mice subjected to an experimental autoimmune myositis (EAM) model. Methods: We measured TLR4-MyD88 pathway related factors, IFN-γ and IL-17A in EAM mice and PM patients.Then we observed the changes of above factors and the inflammatory development of EAM mice with TLR4 antagonist TAK-242, IFN-γ or IL-17A antibody treatment. Results: The expression of TLR4, MyD88, and NF-κB was significantly up-regulated in the muscle tissues both in 22 patients with PM and in the EAM model. As expected, increased levels of various cytokines, such as IL-1β, IL-6, IL-10, IL-12, TNF-α, TGF-β, IFN-γ and IL-17A were evident in the serum of EAM mice. Moreover, mRNA expression levels of IFN-γ and IL-17Awere significantly increased in both PM patients and EAM mice. Consistently, the levels of these factors were positively correlated with the degree of muscle inflammation in EAM mice. However, when EAM mice were treated with TLR4 antagonist TAK-242 the expression of IFN-γ and IL-17Awas decreased. When the cytokines were neutralized by anti-IFN-γ or anti-IL-17A antibody, the inflammatory development of EAM exacerbated or mitigated, respectively. Conclusion: The present study provided the first evidence that the TLR4-MyD88 pathway may be involved in the immune mechanisms of PM by mediating IFN-γ and IL-17A.